2019
DOI: 10.1016/s2468-1253(19)30016-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open adhesiolysis for adhesive small bowel obstruction (LASSO): an international, multicentre, randomised, open-label trial

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
9

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 26 publications
4
54
1
9
Order By: Relevance
“…Minimally invasive surgery has been associated with less formation of adhesions and recent reviews found a reduction of SBO events and surgery for SBO after laparoscopic colorectal surgery compared with after open surgery [22,23]. The increasing reports of laparoscopic SBO-surgery are promising [24]; however, such surgery seems to be most suitable for adhesive bands. There are several adhesion prevention substances on the market, some of which are in a form of a sheet or film, creating a localised protection area.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive surgery has been associated with less formation of adhesions and recent reviews found a reduction of SBO events and surgery for SBO after laparoscopic colorectal surgery compared with after open surgery [22,23]. The increasing reports of laparoscopic SBO-surgery are promising [24]; however, such surgery seems to be most suitable for adhesive bands. There are several adhesion prevention substances on the market, some of which are in a form of a sheet or film, creating a localised protection area.…”
Section: Discussionmentioning
confidence: 99%
“…values were used. χ 2 and Kruskal–Wallis tests were used to test for differences between categorical and continuous variables respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Much of the literature addressing the treatment of small bowel obstruction (SBO) focuses on management of the most common cause, adhesions 1‐3 . Emergency treatment of the obstructed abdominal wall hernia contains knowledge gaps that include the optimal surgical approach and type of repair 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…65 With advances in minimal access technology and increasing experience, LAL is recommended. Laparoscopic adhesiolysis reduces the duration of surgery by 50% (P < 0.001), 66,67 postoperative length of stay (by~1.3-2 days), 68 overall complication rate (P = 0.014) with an adjusted OR of 0.37 (P = 0.002), 69 and adhesion reformation. 70 It is also associated with faster GI recovery (e.g., quicker removal of nasogastric tube and passage of flatus).…”
Section: Surgical Managementmentioning
confidence: 99%
“…Risk of open conversion is higher in patients with dense or diffuse adhesions, previous midline laparotomy, iatrogenic injuries, bowel ischemia or perforation, inadequate exposure, need for bowel resection, non-adhesive etiologies of obstruction (e.g., hernia, malignancies), CT scan findings of free abdominal fluid, distended bowel of ≥4 cm, or small bowel feces sign. 69,68 Open conversion does not increase the rate of complications or morbidity. 36,65,69 As thermal injuries could lead to delayed perforation, surgeons must avoid energy-based dissections, and perform sharp scissor dissection with patience.…”
Section: Surgical Managementmentioning
confidence: 99%